Health, nutrition and food demand [ - Chern, Wen S.; Rickertsen, Kyrre (CABI, 2003)
This book discusses the likely impacts of health information on the demand for various foods in various countries and among various socioeconomic groups. The effects of types of information such as food scares related to mad cow disease and advertising re also discussed. The book serves as reference for researchers in the food industry and government, as well as a supplementary textbook in courses in applied